A huff-and-puff production of gas hydrate deposits in Shenhu area of South China Sea through a vertical well - Su, Zheng; Moridis, George J.; Zhang, Keni; Wu, Nengyou (Journal of Petroleum Science and Engineering, 2012)
The Shenhu area on the northern continental slope of the South China Sea is one of the most promising fields for gas hydrate exploitation. Drilling and sampling has indicated high saturations of methane hydrate in clay silty sediments at drilling site SH2. The hydrate-bearing layer is overlain and underlain by permeable zones of mobile water, and the system does not appear to be bounded by low-permeability strata. In this study a huff-and-puff method is used to producing gas from the hydrate accumulation. We simulate numerically the hydrate dissociation and gas production by alternately injecting hot water and producing fluids at a vertical well. The simulations show the gas production rate in huff-and-puff operations is very small (50-140 m(3)/d), and unacceptable for commercial production. The calculation also indicated secondary hydrates forms at the very early period of injecting operations, and then gas is released due to the thermal stimulation of hot water, but the amount of released gas in the injection periods of hot water is much smaller than that converts into secondary hydrates. In the production operations, much of gas is released from the hydrates due to a small depressurization at the well, but the released gas can not produce effectively due to the small pressure gradient, and thus remains in the reservoir and converts into secondary hydrates in the next operation of injecting hot water. The study provides an insight into the production potential of the Shenhu hydrate accumulations through the huff-and-puff method, and a basis for the analysis of the economic feasibility of gas production from that area. (C) 2012 Elsevier B.V. All rights reserved.